Corrections to Phytotaxa 112: Update on the systematics of Benstonea (Pandanaceae) - Callmander, Martin W.; Buerki, Sven (Phytotaxa, 2013)
After the publication of our Update on the systematics of Benstonea (Pandanaceae): When a visionary taxonomist foresees phylogenetic relationships (Callmander, Booth, Beentje & Buerki 2013), an error was brought to our attention: